Socio Economics of Majidyya village - Dessalegn, Bezaiet (2018)
A field questionnaire campaign was designed and conducted for Muhareb Watershed, which include Muhareb and Al Majidya villages, as well as the neighboring village of Al Ktefeh. In total 50 questionnaires were processed for evaluating local communities baseline and feedback on soil and water conservation activities undertaken.